High School Vocational Counseling Role in Leveraging Students` Professional Inclinations - Gabriel Brătucu; Anca Madar; Nicoleta Andreea Neacşu; Dana Boşcor; Codruţa Adina Băltescu (Amfiteatru Economic)
The experience of many countries with a well-educated workforce highlights the important role of vocational counselling services for advantageous youth professional orientation. Researchers manifest in their turn, a growing interest to study the role of vocational counselling, from the perspective of increasing the efficiency of investment in education and strengthening the capacity of enterprises to meet the challenges of the knowledge economy. In Romania, high school students have access to career guidance services, but there is little information on the extent to which they use or how useful they consider these services. Many times, there is a social conformism among high school graduates, which determines them to choose professions valued at a certain moment, without making a personal judgment. The aim of this paper is to analyse, as a good practice, the role of high school graduate vocational counselling in developing professional skills, in order to help them make the right career decision. In order to monitor the high school students` opinions on the vocational guidance and their perceptions of the integration in the labour market, a market research study has been conducted. This is a survey conducted on a sample of 2,364 high school students in their final year of study (twelve grade). The research has shown that a reduced percentage of the interviewed high school students have knowledge about the vocational guidance activity. From those who have used these services, most of them were satisfied. The study also highlighted the fact that the most important criteria for getting a job are the skills acquired during studies.